Active release coating of multilayer assembled branched and ionic β-cyclodextrins onto poly(ethylene terephthalate). (15th October 2017) - Pérez-Álvarez, Leyre; Ruiz-Rubio, Leire; Lizundia, Erlantz; Hernáez, Estíbaliz; León, Luis M.; Vilas-Vilela, Jose Luis
Highlights: Multilayers of branched and ionic β-CDs were assembled onto films of PET. LbL assembling was monitored by XPS, TEM and labelling with fluoresceinamine. Triclosan (TR) was successfully loaded on prepared PET-βCDs multilayers. Complexation after PET-βCDs multilayers formation led to higher TR loading. TR maximum release took place within the first 10 h. Abstract: Branched ionic cyclodextrins multilayers were assembled onto the surface of previously aminolyzed poly(ethylene terephthalate) in order to construct local drug delivery tailored platforms with potential applicability as materials for indwelling medical devices. The construction of the multilayers took place by the alternate deposition of ionic cyclodextrin derivatives and was characterized by surface zeta-potential measurements, X-ray photoelectron spectroscopy and, after fluorescent labeling of anionic branched cyclodextrins, by UV–vis spectroscopy and confocal fluorescence spectroscopy. Transmission electron microscopy is used for the first time to show the deposited coating, and an average thickness of ∼270 nm for 20 bilayered covering was measured. Contact angle measurements showed great differences in the films as the number of cyclodextrin layers was increased, and highly hydrophilic (19.7 ± 1.5° for 10 bilayers) surfaces were obtained. The loading and release capacity of the antimicrobial triclosan, as hydrophobic model molecule, from PET coated surfaces was also studied.